FACTORS AFFECTING REPURCHASE INTENTION: THE CASE STUDY OF Rumah.com - Marine Novita; Margaretha Pink Berlianto (Jurnal Ekonomi, 2023)
The year of the pandemic is the hardest year that everyone can imagine. Every industry got affected and on of them is property industry. Thus, this research examine Rumah.com as one of the big players in the property industry to see the intention to repurchase of property through its platform. In order to do that, this research had collected 418 respondents that have used Rumah.com. The result showed that every single variable to have a positive relation with intention to repurchase.